Hop Test Symmetry Scores Early after Rehab Predict Successful 2 Year Outcomes of ACLR. Issue 7 (21st July 2017) - Failla, Mathew; Zarzycki, Ryan; Logerstedt, David; Wellsandt, Elizabeth; Axe, Michael J.; Snyder-Mackler, Lynn
Objectives: Return to pre-injury function, return to pre-injury activity, and avoiding repeated knee joint instability are common goals of anterior cruciate ligament reconstruction (ACLR). None of these goals, however, are guaranteed through surgical intervention. Clinical test batteries are able to differentiate between those with good and poor knee function after ACL injury, but the usefulness of this battery after reconstruction to predict longer-term outcomes is unknown. The purpose of this study is to determine if a test battery consisting of clinical, functional, and patient-reported measures 6 months after surgery is predictive of a successful outcome 2 years after ACLR. Methods: This is a secondary analysis of prospectively collected data. Seventy-three athletes after acute, isolated, unilateral ACL rupture were included in this analysis. All subjects underwent ACLR, and returned for follow-up testing at 6 and 24 months after reconstruction. A test battery consisting of quadriceps strength symmetry (QI), 6-meter timed hop test symmetry (TimHP), the Knee Outcome Survey Activities of Daily living (KOS), and the Global Rating (GLO) was administered 6 months after reconstruction. At 2 year follow-up, all athletes completed the International Knee Documentation Committee Subjective Knee Form 2000 (IKDC) and self-reported whether they had returned to their pre-injury sports and if they had a second ACL injury to the ipsilateral or contralateral knee. A successful outcome was considered achieving at least the 15 th percentile of age and sex matched IKDC normative values, returning to pre-injury sports, and not having a second ACL injury at 2 years. Logistic regression was used to predict a successful outcome 2 years after ACLR. Receiver operating characteristic curve (ROC), positive and negative likelihood ratios were calculated for any statistically significant individual predictors. Significance was set at .05 a priori. Results: Fifty-five (75%) of the 73 athletes had a successful outcome. There were no differences between groups in age, sex, graft type or body mass index (p >.05). The test battery performed 6 months after ACLR was predictive of 2 year success (r 2 =.307;p=.005). The TimHP (p=.018; exp(b)=1.11) was the only significant individual predictor in the test battery. Maximizing sensitivity and specificity (Table 1), a cutoff score of 96% symmetry for the TimHP had a positive likelihood ratio of 1.95 and a negative likelihood ratio of 0.4. Conclusion: A test battery of clinical, functional, and patient-reported measures was predictive of success 2 years after ACLR. Achieving 96% symmetry on the 6-meter timed hop test 6 months after ACLR was associated with almost twice the probability of a successful outcome while not achieving that cutoff was associated with 2.5 times less likely of having a successful outcome. Return to sport criteria have typically suggested 85-90% symmetry cutoffs, and this work suggests those cutoffs might be too low. While delaying return to sport for high risk athletes is warranted, clinical and functional measures should still be maximized early after ACLR to optimize outcomes. Table 1: Discriminate and ROC Curve Analysis of 6-Meter Timed Hop Symmetry Scores TimHP Successful Unsuccessful Total Pass 41 4 45 Fail 14 14 28 Total 55 18 73 Optimum Cutoff Sensitivity Specificity Positive Likelihood Ratio Negative Likelihood Ratio TimHP 96 .750 .615 1.95 0.40